Volume 2: Structures, Safety and Reliability 2008
DOI: 10.1115/omae2008-57584
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation Into Parameters Influencing the Installation of Suction Caissons in Sand

Abstract: This paper reports results from a numerical investigation into the suction caissons penetration in sand. Two dimensional axisymmetric models have first been calibrated and verified against several laboratory and field test data from other researchers. Soil nonlinearities and soil/caisson interactions have been taken into account. The verified models have then been used to evaluate the effects from various soil/structure characteristics on the performance of the suction caissons during the installation phase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…has already been investigated by a number of researchers (Bang et al 2000;Cassidy et al 2006;Narasimha Rao et al 2006;Zeinoddini et al 2010). Some previous numerical investigations indicated that positively tapered suction caissons may provide pull-out capacities considerably higher than that of their equivalent upright caissons Zeinoddini et al 2008a;Zeinoddini et al 2008b;Zeinoddini, Hobbi, et al 2009;Zeinoddini, Keyvani, et al 2009). A thorough evaluation of the performance of tapered suction caissons requires further studies, particularly, experimental investigations.…”
Section: Introductionmentioning
confidence: 93%
“…has already been investigated by a number of researchers (Bang et al 2000;Cassidy et al 2006;Narasimha Rao et al 2006;Zeinoddini et al 2010). Some previous numerical investigations indicated that positively tapered suction caissons may provide pull-out capacities considerably higher than that of their equivalent upright caissons Zeinoddini et al 2008a;Zeinoddini et al 2008b;Zeinoddini, Hobbi, et al 2009;Zeinoddini, Keyvani, et al 2009). A thorough evaluation of the performance of tapered suction caissons requires further studies, particularly, experimental investigations.…”
Section: Introductionmentioning
confidence: 93%